Pengaruh Penyuluhan Jajanan Sehat Terhadap Pengetahuan Dan Sikap Siswa Di Madrasah Ibtidaiyah Gonilan Kartasura - Lestari, Shinta Asih Witha; , dr. M. Shoim Dasuki, M.Kes; , dr. Anika Candrasari, M.Kes (2015)
Background : Snacks are closely assosiated with students. From BPOM survey showed that 99% of students buy the snacks at school. The snacks are bought didn't know whether it is safe and clean or not, so it needs a special strategy to know how to choose the healthy snacks. Objective : To analyze the influence of healthy snacks education of the knowledge and attitudes of the students at Madrasah Ibtidaiyah Gonilan Kartasura. Methods : This research used quasi experiment. The sample of this experiment was the VI grades of Madrasah Ibtidaiyah Gonilan Kartasura. The sample was 35 respondents that got education about healthy snacks. Data take from the questionnaire pre test, post test 1and post test 2 did 2 weeks after the education. Data analyze used Repeated ANOVA and Friedman test. Result : There was significant different between two measurement data to knowledge was seen from Friedman test that continued by pos hoc Wilcoxon and got sig value p = 0,000 (p<0,05). Next for the attitudes, there was different attitudes value from two data was seen from Repeated ANOVA test and got sig value p=0,000 (p<0,05). The way to know the different between three measurement was seen from the result of Pairwaise Comparisons test with sig value p=0,000 that mean there was difference in all measurements. Conclusion : There was the influence healthy snacks education of the knowledge and attitudes of students at Madrasah Ibtidaiyah Gonilan Kartasura.